Samsung Galaxy S10 For Dummies - Hughes, Bill (For Dummies, 2019)
The bestselling guide to your new Samsung This book documents all the features and capabilities of Samsung Galaxy S10 device, approaching them from the point of view of a user who is intimidated by the technology and baffled by the documentation and online support that comes with the phones. All aspects of the suite of devices are covered, from setup and configuration, to extensive use of the phone features and capabilities: texting, e-mailing, accessing the Internet, maps, navigation, camera and video, social networking, taking pictures, watching movies, downloading apps, synching with a PC, and expanding the phone's potential with new software releases. The accessible and fun writing style provides clear direction and doesn't hinder the book's important content and coverage. Readers will keep this book close by, referring to it often as they explore the features of their new Samsung Galaxy S10 smartphone. Navigate your phone Use mobile data technology Send and receive messages Have fun with apps If you're baffled by the documentation and online support that comes with your phone, your solution is here!